Philosophical Views of I.Yusupov - Orazbayev , Arislanbay (Pubmedia Social Sciences and Humanities, 2025)
Ibrahim Yusupov, a distinguished poet of Uzbekistan and Karakalpakstan, is renowned for his philosophical poetry, which deeply connects the themes of homeland, human nature, and personal emotions. This article explores the way Yusupov’s works address the emotional and philosophical dimensions of life, with a particular focus on his portrayal of his homeland, the Motherland, and his relationship with his mother. Through a close analysis of his poems, such as "Watan" and "Men qalada oqıǵanda," the article highlights the symbolic use of natural imagery and emotional depth to express complex ideas about identity, belonging, and love. Yusupov’s poems reflect the evolution of his poetic thought, moving from youthful romanticism to profound social and political reflections. This study emphasizes the poet’s skill in blending personal experiences with universal philosophical themes, shedding light on his contribution to the development of Karakalpak and Uzbek literature. The article also discusses Yusupov's poetic philosophy, his portrayal of human struggles and joys, and his enduring influence on national identity and cultural consciousness.